ナンキョクサンギョ Notothenia neglecta Nybelin サイハ ノ ケイタイ ト セツジ ニ サイシテ ノ セイタイガクテキ キノウ - Rios, Flavia Sant'Anna; Fanta, Edith (1998)
P(論文) 南極, 亜南極海域の固有種であるNotothenia neglectaは基本的には食肉性であるが, 食物選択の範囲は広い。多様な餌料を捕食することに関連して, 本種の鰓耙はどの様な形態をとっているかを評価するために, サウスシェトランド諸島, キングジョージ島のアドミラルティ湾で標本採取を行った。本種の異内容物の同定と大きさの計測を行い, 咽頭鰓節器官の肉眼的, 顕微鏡的観察を行った。鰓耙の形態と胃内の餌生物の大きさは, 本種が魚食性であるとともに, 他の小型餌生物をも捕食することができることを示している。鋭い絨毛状小歯を持つ鰓耙は, 餌の保持力を強め, 前端に位置する鰓耙はしなやかで小歯を欠き, 大きな餌をゆっくり摂取する際にも, 連続して呼吸が可能な構造である。餌生物の選別はサイズでなされる。鰓耙間隔は, 体長の0.17%以上のサイズの端脚類, 二枚貝類, 巻貝類であれば摂取できる距離である。餌料は味蕾と化学感覚細胞に依り化学的に選別される。杯細胞は粘液を分泌し餌料を包み, 摂餌に際して粘膜を傷つけぬようにすると同時に, 小型の餌生物をまとめる。N. neglectaはさまざまな食物発見, 選択メカニズムを持つ活発な捕食者として, 季節に応じて餌料の組成が変るという, 自然環境下においても生き残り得る。 Notothenia neglecta, endemic to the Antarctic and sub-Antarctic regions, is basically carnivorous with a wide dietary spectrum. In order to evaluate the gill rakers' morphology and histological features of gill structures in relation to their feeding habits, specimens were obtained at Admiralty Bay (King George Island, South Shetlands). Their stomach content was identified and measured and the pharyngobranchial apparatus was studied macro and microscopically. The morphology of the gill rakers and the sizes of prey that are present in the stomach of N. neglecta characterize this species as piscivorous but also able to capture other small prey. Gill rakers provided with sharp villiform denticles improve the retention of fish. At the anterior row, gill rakers are flexible and without denticles, allowing continuous breathing during slow ingestion of large prey. Food is selected by size. The distance between gill rakers allows the retention of amphipods, bivalves and gastropods if bigger than 0.17% of the predator standard length. Food is also selected chemically by taste buds and isolated chemical-sensorial cells. Goblet cells produce mucus that covers the preys with a smooth layer, avoiding scratching of the mucosa during ingestion of food and promoting aggregation of smaller food items. N. neglecta is an active feeder that uses different detection and selection mechanisms to survive in an environment where the food composition varies during the year. ...